Sources of variation in first language acquisition languages, contexts, and learners - Hickmann, Maya; Veneziano, Edy; Jisa, Harriet (Trends in language acquisition research ;, 2018)
Developmental research has long focused on regularities in language acquisition, minimizing factors that might be responsible for variation. Although researchers are now increasingly concerned with one or another of these factors, this volume brings together research on three different sources of variation: language-specific properties, the nature of the input to children across contexts, and several aspects of the learners themselves. Chapters explore these sources of variation within an interdisciplinary and comparative approach allying theories and methodologies stemming from linguistics, psycholinguistics, developmental psychology, and neuroscience. The comparative perspective involves different languages, contexts of use, types of learners (first/second language acquisition, monolingual/bilingual learners, autism, language impairment), as well as vocal and visuo-gestural communicative modalities (co-verbal gestures, sign language acquisition). The volume points to the need to enhance interdisciplinary research using complementary methodologies to further examine sources of variation and to integrate variation into a more general developmental theory.